The Roles of the Church in Helping the Depressed - Fransius Kusmanto; Sarah Putri Waruwu; Fransisca Adelia Serenity (SANCTUM DOMINE: JURNAL TEOLOGI, 2022)
The Covid-19 pandemic calls the church to manifest diaconal duties, especially in helping congregations who are emotionally affected. Gereja Persekutuan Pemberitaan Injil Kristus Maranatha, Singkut Durian tries to take a role to assist the congregation members who is experiencing mental problems due to this pandemic season. This study was conducted to find out what roles the church can take to provide assistance to congregations who are experiencing problems due to this pandemic. Descriptive qualitative method employed in this research with observations and field interviews to gather data from the field. The study also used a variety of literature and previous research findings related to the topic. The results obtained in this study are: the church required to provide a room and counseling staff, resources, empowerment programs, and various skills training.